Assessing the relationship between walkability factors and walking behaviours among university students using structural equation model (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Walkability in university campuses has attracted more attention in Malaysia due to its influence on student health, mobility, and environmental sustainability. However, few studies have examined the determinants of walking behaviour in local higher learning institutions. This study investigates the relationship between determinants of walkability and walking behaviours among students at Universiti Malaysia Kelantan (UMK), Bachok Campus. A quantitative approach was adopted to gain deeper insights into the determinants of pedestrian behaviours. Quantitative data were collected from a purposive sample of 300 students through a structured survey in May and June 2024 and were analysed using SPSS Version 28.0 and AMOS. This study reveals that among the three factors encouraging walkability on campus, only Amenities and Environmental Factors significantly influence student walking behaviours. In contrast, despite high ratings, Pedestrian Safety and Infrastructure factors showed no statistical effect. These findings highlight the importance of campus environments enriched with amenities and environmental features in shaping students' walking behaviours. Prioritising such elements can promote more active, sustainable, and engaging mobility patterns across the campus.
Keywords: Walkability factors; walking behaviours; campus; structural equation model